Visum et Repertum Socialization by RRI Medan Radio Broadcasting - Petrus, Asan (Jurnal Kedokteran Universitas Lampung, 2019)
Background; Visum et repertum (VeR) as a form of report on the results of examinations of victims of crime, both living victims and death victims, is one of the services provided by doctors who can help law enforcement in upholding justice. Visum et Repertum as evidence that plays a role in the process of proving a criminal case against the health and mentality of humans certainly requires a form that is informative and correctly made. But in reality, based on several studies, it was found that VeRs are mainly made with poor quality, including in PKU Muhammadiyah Jogja Hospital (27.4%) 1, in Arifin Pekanbaru Hospital (37.11%), in Dumai Hospital (37.46%) 2 and several other service units that have been studied are also not much different. That is why we, from the Forensic Department of Faculty of Medicine of USU, are very concerned about this. In our collaboration with RRI Pro 1 FM 94.3 conducting an interactive dialogue about VeR. Method; interactive dialogue through RRI Medan radio broadcasts. Results; currently it cannot be evaluated, we hope that in the next 5 years we will get the desired change. Discussion; based on previous research that mainly VeR is considered poorly made so that the Department of Forensics through cooperation between RRI Medan and the Faculty of Medicine of USU conducted an inspirational interactive dialogue broadcast with the theme of the VeR in addition to the Forensic Department with the above objectives also actively conducting research activities, seminars , training related to the making of VeR, and because this activity is an initial activity, it cannot be evaluated right away. We hope that in the next 5 years there will be a change in the result of good quality VeR. Conclusion; VeR socialization activities through interactive dialogue on RRI radio broadcasts are one of the ways sought by the Forensic Department to improve the ability of general practitioners in making VeR.